Influence of diet and manure management on ammonia and greenhouse gas emissions from dairy barns. (18th June 2019) - Edouard, N.; Charpiot, A.; Robin, P.; Lorinquer, E.; Dollé, J.-B.; Faverdin, P.
Abstract : Dairy systems are a source of pollutant emissions, such as greenhouse gases (GHG ) and NH3 that are associated with impacts on the environment. Gas emissions in barns are related mainly to diet intake and chemical composition, N excretion and manure management. A reduction in dietary N is known to be an effective way to reduce N excretion and the resulting NH3 emissions. However, most studies consider manure in liquid form with frequent removal from the barn. In deep litter systems, several processes can occur during the accumulation of solid manure that result in variable gas emissions. The objective of this experiment was to investigate the influence of the interaction between dietary CP (low or high) and manure management (liquid or solid) on gas emissions (NH3, N2 O, CH4 ) at the barn level. Dietary treatments provided either low (LowN ; 12% CP) or high (HighN ; 18% CP) degradable protein to modify the amount of total ammonia nitrogen (TAN ) excreted. The cows were housed for two 8-week periods in two mechanically ventilated rooms equipped to manage manure either in liquid (LM ; slurry) or solid form (SM ; deep litter). In the LM treatment, N balance was measured for 4 days. As expected, animals fed the LowN diet ingested 35% less N and excreted 65% less N in their urine, with no reduction in faecal N excretion and N secretion in milk. On the LowN diet, excretion of urea-N and NH3 -N emissions were reduced regardless of the manure management. On the HighN diet, urinary urea-N excretion was three times as high, while NH3 -N emissions were 3.0 and 4.5 times as high in LM and SM, respectively. Manure management strongly influenced CH4 -C emissions, which were 30% higher in SM than in LM, due to the accumulation of litter. Moreover, gas emissions from solid manure increased over the accumulation period, except for NH3 on the LowN diet. Finally, our results suggest that methods used for national inventories would become more accurate by considering the variability in TAN excretion, which is the primary factor that influences NH3 emissions.